(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the linguacultural features of metaphorical expressions in literary texts-based Bronte E. and Dickens C. The article’s subject matter is related to the study of English-language paremias, which reflect the unique character of native speakers and culture, so they are always in the center of attention of cultural scientists. As a result, the article presents linguacultural concepts and models that determine the features of paremic metaphorical images.